Convergence Epistemology of Legal Studies Based on Revelation - Prasetyo, Yogi (NAJAHA, 2022)
The demand for truth between the epistemology of normative legal science and the epistemology of legal sociology in Indonesia needs to develop positively. It can be said to be experiencing stagnation. Therefore, it is necessary to reform the epistemology of fiqh from other discourses, such as those contained in natural law based on religious revelation which touches on substantial aspects of the spiritual moral values of humans as creatures of God. This research aims to analyze the epistemology of revelation-based legal science convergence. The basis for using scientific epistemology based on revelation is developments in the times when people are experiencing a multi-dimensional crisis due to the wrong way of thinking of themselves because they have ignored the role of God in regulating human life. This research is library research. Based on the theories and concepts used, the primary data source is literature study material which discusses the theory and concept of the convergence of jurisprudence epistemology from Khudzaifah Dimyati regarding Thinking & theorizing jurisprudence. The data analysis was carried out using an interpretive descriptive method. The study results show that in the holy books and the values of religious teachings, legal science, the truth values contained therein are recognized by rational logic and empirical reality, but can also be recognized as valid and eternal. The epistemology of God-based revealed law as in the science of prophetic law has dimensions of humanization, liberation and tridentity that can guide and guide humans to achieve a better and more authentic life.